Patient comfort scores do not affect endoscopist behavior during colonoscopy, while trainee involvement has negative effects on patient comfort - Chan, Brian P.H.; Hussey, Amanda; Rubinger, Natalie; Hookey, Lawrence C. (Endoscopy International Open, 2017)
Introduction Patient comfort is an important part of endoscopy and reflects procedure quality and endoscopist technique. Using the validated, Nurse Assisted Patient Comfort Score (NAPCOMS), this study aimed to determine whether the introduction of NAPCOMS would affect sedation use by endoscopists.Patients and methods The study was conducted over 3 phases. Phase One and Two consisted of 8 weeks of endoscopist blinded and aware data collection, respectively. Data in Phase Three was collected over a 5-month period and scores fed back to individual endoscopists on a monthly basis.Results NAPCOMS consists of 3 domains – pain, sedation, and global tolerability. Comparison of Phase One and Two, showed no significant differences in sedative use or NAPCOMS. Phase Three data showed a decline in fentanyl use between individual months (P = 0.035), but no change in overall NAPCOMS. Procedures involving trainees were found to use more midazolam (P = 0.01) and fentanyl (P = 0.01), have worse NAPCOMS scores, and resulted in longer procedure duration (P < 0.001). Data comparing gastroenterologists and general surgeons showed increased fentanyl use (P = 0.037), decreased midazolam use (P = 0.001), and more position changes (P = 0.002) among gastroenterologists.Conclusions The introduction of a patient comfort scoring system resulted in a decrease in fentanyl use, although with minimal clinical significance. Additional studies are required to determine the role of patient comfort scores in quality control in endoscopy. Procedures completed with trainees used more sedation, were longer, and had worse NAPCOMS scores, the implications of which, for teaching hospitals and training programs, will need to be further considered.